Sweetening Pharmaceutical Radiochemistry by 18F-Fluoroglycosylation: Recent Progress and Future Prospects - Sandip S. Shinde; Simone Maschauer; Olaf Prante (MDPI AG, 2021)
In the field of 18F-chemistry for the development of radiopharmaceuticals for positron emission tomography (PET), various labeling strategies by the use of prosthetic groups have been implemented, including chemoselective 18F-labeling of biomolecules. Among those, chemoselective 18F-fluoroglycosylation methods focus on the sweetening of pharmaceutical radiochemistry by offering a highly valuable tool for the synthesis of 18F-glycoconjugates with suitable in vivo properties for PET imaging studies. A previous review covered the various 18F-fluoroglycosylation methods that were developed and applied as of 2014 (Maschauer and Prante, BioMed. Res. Int. 2014, 214748). This paper is an updated review, providing the recent progress in 18F-fluoroglycosylation reactions and the preclinical application of 18F-glycoconjugates, including small molecules, peptides, and high-molecular-weight proteins.